Znaczenie i funkcja motywu klonu w warmińsko-mazurskich pieśniach ludowych - Lechocka, Ewelina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
This article is an analysis of maple motives, which occurred in collection of Warmian and Masurian folk songs elaborated in XIX and XX century. The purpose of this study was to define meaning and function botanic vocabulary mentioned in folkloristic texts and to compare poetic representation of maple motif with its role in every-day-life and culture of Warmia and Masuria’s inhabitants. As it was deducted from maintained analysis, the folk output and botanic themes are a valuable source of information about identity of rural population from Warmia and Masuria territories. Utilization of maple motif in folksongs is characteristic for its strong resemblance to empiric reality, in which the plant plays a great role in every-day-life and in immaterial culture.